Music therapy and anxiety in Cuban adult patients undergoing tooth extractions - Alain Manuel Chaple-Gil; Solanch de la Caridad Damas Heredia; José Armando Galván-Cabrera; Maicel Eugenio Monzón Pérez; Kelvin Ian Afrashtehfar (Revista Habanera de Ciencias Médicas)
Introduction: Music therapy is a scientific discipline that can influence the decrease of anxiety during medical procedures.